The influence of HIV on return to work in stroke survivors amongst a population in the eThekwini district, Kwazulu-Natal - Naidoo, Wesley (My University, 2022)
Background Work is considered a life role. A return to work (RTW) process considers biopsychosocial factors together with the interaction of systems and stakeholders as determinants of work-related disabilities and participation. Stroke survivors often struggle to be or remain employed. As Human Immunodeficiency Virus (HIV) can increase the risk of stroke development, the economically active population are financially impacted from resultant disability. It is therefore paramount to ascertain the importance of quality of life (QoL) and economic outcomes amongst people living with HIV (PLHIV) contemplating a RTW. No study has explored the influence of HIV on RTW in stroke survivors. Aim of the study: To explore the influence of HIV in stroke survivors who either have or have not RTW. Method Twelve PLHIV who are stroke survivors with a history of employment prior to stroke onset were recruited from a hospital database of an antiretroviral/ human immunodeficiency (ARV/HIV) clinic to partake in a qualitative study. Using a phenomenological approach, data was collected using a demographic questionnaire and semi-structured interview. The semi-structured interview data was transcribed and analysed using an inductive thematic analysis. The study was conducted at a rehabilitation department of a regional hospital in the eThekwini district, Kwazulu-Natal. Results Two participants were in a pilot study with the remaining twelve participants in the main study. Participants were of a mean age of 39 years old, equally distributed as male to female and all were on ART. Only two participants were working at the time of the study. The physical and cognitive impacts resulting from the stroke sequalae largely affected their outlook on RTW. The engagement of healthcare services such as psychotherapy and counselling with other RTW enabling professionals provided a gateway to continued employment in the face of potential HIV disclosure at the workplace. An economically productive RTW process, which included the nullification of societal and work related barriers, is promoted by ART consideration, family support, the restoration and maintenance of employment benefits. Interestingly, the prosperity for a better QoL and RTW via new job opportunities, mitigating the impact of one’s altered health status on work suitability and an improved socioeconomic status were plausible. Conclusion Health education, especially at the workplace, would encourage a disclosure of both HIV status and ART use for HIV positive stroke surviving employees. Participants mentioned that employers should consider their employee’s health to allow time away for medical care and still continue productivity at the workplace in their absence. Having a support structure including related support services, an opportunity to maintain employment and being empowered by RTW professionals can inform prospective employment decision-making processes which can minimize the negative effects of unemployment on the QoL of this population.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021